Analisis Keefektifan Penerapan Kurikulum Merdekan di SMP Negeri 1 Sawo - Sararateoli Telaumbanua; Kristiani Telaumbanua; Asal Niat Halawa; Noveri Amal Jaya Harefa (Journal on Education, 2024)
The purpose of this study was to determine the effectiveness of the implementation of the independent curriculum at SMP Negeri 1 Sawo. This research uses a qualitative descriptive method. The research instruments used were interviews and documentation. The research object used is the effectiveness of the implementation of the independent curriculum. The subjects in this study were the principal, 3 teachers and 6 students. The data sources used in this research are primary data sources. The data analysis techniques used are data reduction, data presentation and data verification / conclusion drawing. Based on the results of the analysis conducted by the researcher, it can be concluded that the implementation of the independent curriculum at SMP Negeri 1 Sawo is effective.